Sharp Turn to the Market. Economic Reform in Russia (1992-1998) and Its Consequences - Tatarkin, Alexander Ivanovich; Bersenyov, Vladimir Leonidivich (Economy of Regions, 2016)
The generalization and systematization of the literature on the history of reforms accumulated for twenty years allow to organise the ideas of the transformations processes and to set a new vector of understanding the socio-economic development of Russia in the last decade of the 20th century - the first decades of 21st century. The first step is the analysis of the publications reflecting the preparation, a course and results of a modern economic reform in the 1990th. The historiographical review includes the monographs written by both apologists of «shock therapy», and their opponents and critics, first of all by Academicians of the Russian Academy of Sciences. This literature analysis reveals the range of opinions concerning the preference of a «shock» variant of transformations, the assessment of the results of the reform by the end of the 1990th and the possibilities of the alternative ways of transition from the planned to the market economy. In particular, the apologists of «shock therapy» refer to the threat of hunger and civil war to justify the decisions, which have caused the decline in production, a hyperinflation and other negative tendencies. Their critics note that a lack of the support of the population has caused a failure of market transformations. While recognizing the obvious, that is an essential deterioration of economic indicators, the apologists see their success in the development of a system of market institutions and consequently, insist that there was no alternative to the realized reform. In turn, their opponents believe that there were the alternatives of «shock therapy», and the gradual cultivation of the institutions of the market economy would be their distinctive feature, but not their introduction by the administrative order.